Fire tests on wood products subjected to different heat fluxes - Mačiulaitis, Romualdas; Praniauskas, Vladas (Journal of Civil Engineering and Management, 2010)
The paper analyses three different wood products used for research exposing them to the surface heat flow density of 30 kW/m2, 50 kW/m2 and 70 kW/m2 and applying the test method described in ISO 5660–1 Reaction‐to‐fire tests – Heat release, smoke production and mass loss rate – Part 1: Heat release rate (Cone calorimeter method). Research was performed applying 18 mm and 29 mm thick laminated wood chipboards and 24 mm thick medium density fibreboard. The paper provides an overview of the fire properties of wood products and discusses testing methods and the percentage composition of the tested wood products. Mean time to their ignition was determined. The mean values of the maximum heat release rate and time required to achieve them were investigated. Furthermore, the measurements of the released heat and efficient heat of combustion were taken. Further research covers the performance of statistic analysis, deriving empiric equations, correlation and determination coefficients, standard errors and Student criterion. The results of research are summarized. Conclusions are provided at the end of the paper.First Published Online: 10 Feb 2011